COVID-19 Pandemic and Vaccines Update on Challenges and Resolutions - Khan, Wajihul Hasan; Hashmi, Zohra; Goel, Aditya; Ahmad, Razi; Gupta, Kanisha; Khan, Nida; Alam, Iqbal; Ahmed, Faheem; Ansari, Mairaj Ahmed (Frontiers in Cellular and Infection Microbiology, 2021)
The coronavirus disease (COVID-19) is caused by a positive-stranded RNA virus, called Severe-Acute-Respiratory-Syndrome-Coronavirus-2 (SARS-CoV-2), belongs to Coronaviridae family. This virus originated in Wuhan city of China and became cause of multiwave pandemic that killed 3.46 million people worldwide until May 22nd, 2021. The havoc intensified with emergence of SARS-CoV-2 variants (B.1.1.7; Alpha, B.1.351; Beta, P.1; Gamma, B.1.617; Delta, B.1.617.2; Delta-plus, B.1.525; Eta, and B.1.429; Epsilon etc.) due to mutation generated during replication. More variants may emerge to cause additional pandemic waves. The most promising approach for combating viruses and their emerging variants lies in prophylactic vaccines. Several vaccine candidates are being developed using various platforms, including nucleic acids, live-attenuated-virus, inactivated virus, viral vectors, and protein-based subunit vaccines. In this unprecedented time, twelve vaccines against SARS-CoV-2 have been phased out following WHO approval, while 184 are in preclinical stage and 100 are under clinical development process. Many of them are directed to elicit neutralizing antibodies against viral spike protein (S), to inhibit viral entry through ACE-2 receptor of host cells. Inactivated vaccines, in contrary, provide a wide range of viral antigens for immune activation. Being intracellular pathogen, the cytotoxic CD8+ T cell (CTL) response remain crucial for all viruses including SARS-CoV-2 needs to be explored in detail. In this review, we have tried to describe and compare approved vaccines against SARS-CoV-2, that are currently being distributed either after phase-III clinical trials or as emergency use. We have discussed immune responses induced by various candidate vaccine formulations, benefits, potential limitations, effectiveness against variants, future challenges like antibody-dependent-enhancement (ADE), vaccine safety issues and their possible resolutions. Most of the current vaccines developed against SARS-CoV-2 are showing either promising or compromised efficacy against new variants. Multiple antigen-based-vaccines (multivariant-vaccines) should be developed on different platforms to tackle future variants. Alternatively, the recombinant-BCG, containing SARS-CoV-2 multiple antigens, as live-attenuated-vaccine should be explored for long-term-protection. Irrespective of their efficacy, all vaccines are efficient in providing protection from disease severity. We must insist on the vaccine compliance for all age groups and work on vaccine hesitancy globally to achieve herd immunity and eventually to curb this pandemic.